The Abolition of Forced Labor in Vietnam: Is it Compatible with ILO's Standards? - Nguyen, Huyen Thanh; Nguyen, Thang Chien (Journal of Southeast Asian Human Rights, 2025)
The article analyzes the legal problems in the identification of forced labour and the provisions for the abolition of forced labour in Vietnamese law in comparison with the core international labour standards on the abolition of forced labour. This article points out the inappropriate and unspecific points in the law on the abolition of forced labour in Vietnam. Furthermore, the paper analyzes the current situation of forced labour in Vietnam, as well as difficulties in the process of law enforcement on the abolition of forced labour due to the lack of harmonization with basic international labour standards. To study this issue, the author has used a number of research methods such as analysis, synthesis, and comparison of laws based on relevant data collected and processed. On that basis, the article puts forward a series of far-reaching solutions. These meticulously crafted solutions are not only aimed at strengthening the current legal framework but also at significantly improving enforcement mechanisms. This comprehensive approach seeks to foster a remarkably resilient and resolute implementation of the law, with a focused objective of eradicating the issue of forced labour from every nook and cranny of Vietnam's intricate labour landscape.